Synthesis, Spectral Characterization and Stability Studies of Spiroborate Ester of Curcumin with Salicylic Acid - John , Jeena; Rugmini, Sudha Devi; Sreedharan Nair, Balachandran (Novel Aspects on Chemistry and Biochemistry Vol. 1, 2023)
A spiroborate ester of curcumin (CBS) was synthesized using salicylic acid as a ligand to study the kinetics of its thermal and hydrolytic degradation. The structure of the prepared compound was characterized by UV-Visible spectra, IR spectroscopy, and NMR spectroscopy. The isothermal and non-isothermal thermogravimetric method was used to study the thermal decomposition of CBS at different heating rates in a nitrogen atmosphere. The hydrolytic stability of the spiroborate ester was investigated in an aqueous acetone system with different water percentages and temperatures. The activation energies of hydrolysis were calculated using the Arrhenius equation, and the relevant thermodynamic parameters were calculated using the Eyring equation. A plausible mechanistic route for the hydrolysis of the complex was suggested.